1985
DOI: 10.1163/26660644-05502008
|View full text |Cite
|
Sign up to set email alerts
|

A New Genus and Two New Species of Subterranean Amphipod Crustaceans (Hadziidae) from the Bahamas and Turks and Caicos Islands

Abstract: Bahadzia, new genus, and two new species of amphipod crustaceans are described from anchialine caves in the Bahamas and Turks and Caicos Islands. One of the species is recorded from three caves on Grand Bahama Island and one cave on Great Abaco Island, whereas the other species is recorded from two caves on the island of Providenciales. The new genus is apparently more closely related to Metaniphargus and Saliweckelia than other hadziid genera in the peri-Caribbean region, but it also shares some important cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…To date, eleven species of amphipods have been recorded from subterranean habitats of the Yucatán Peninsula, belonging to five families (Ampithoidae, Hadziidae, Hyalidae, Hyalellidae, and Melitidae) (e.g., Holsinger 1977, 1990, 1992, Alvarez and Iliffe 2008, Marrón-Becerra et al 2014, Ortiz and Winifield 2015, Trujillo-Pisanty et al 2010). Among them, six species are classified as stygobionts; they bind solely to aquatic subterranean habitats, exhibiting various degrees of morphological, physiological and behavioural adaptations to life in the hypogean environment (Notenboom 1991).…”
Section: Introductionmentioning
confidence: 99%
“…To date, eleven species of amphipods have been recorded from subterranean habitats of the Yucatán Peninsula, belonging to five families (Ampithoidae, Hadziidae, Hyalidae, Hyalellidae, and Melitidae) (e.g., Holsinger 1977, 1990, 1992, Alvarez and Iliffe 2008, Marrón-Becerra et al 2014, Ortiz and Winifield 2015, Trujillo-Pisanty et al 2010). Among them, six species are classified as stygobionts; they bind solely to aquatic subterranean habitats, exhibiting various degrees of morphological, physiological and behavioural adaptations to life in the hypogean environment (Notenboom 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This genus presently contains three species: B. williamsi Holsinger, 1985, from Great Abaco and Grand Bahama (two islands on the Little Bahama Bank), B. stocki Holsinger, 1985, from Providenciales (in the Turks and Caicos Islands), and B. latipalpus Stock, 1985, from Haiti. The last is a species from flesh groundwaters, whereas the others, including the presently examined specimens, are all from anchihaline cave waters of high salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Bahadzia latipalpus was collected from fresh and oligohaline well water (Stock, 1985) and B. jaraguensis was taken from weakly brackish water on the cave floor in mats of filamentous green algae (Jaume and Wagner, 1998). It is perhaps significant that Mayaweckelia and Tuluweckelia also occur in either fresh or weakly brackish water (Holsinger, 1977(Holsinger, , 1990 and that an earlier cladistic analysis by Holsinger (1992) of 'weckeliid group' genera and the genus Bahadzia suggested that Mayaweckelia and Tuluweckelia are sister genera to Bahadzia. Our present analysis offers further support of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Family HADZIIDAE Karaman, 1943 Genus Bahadzia Holsinger, 1985 (in Holsinger andYager, 1985) Bahadzia caymanensis n. sp. Diagnosis.…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation